‘Deviant’ Or Criminal? On-field ‘Sports Violence’ and the Involvement Of Criminal Law In English Rugby Union - HARDMAN, RORY,MATTHEW (2019)
Like many contact sports, rugby union has danger at its core, and those acts deemed acceptable within rugby would likely be termed ‘violence’ were it to happen away from the sporting arena. This thesis embarks on an exploration of legal interference in on-field ‘violence’ cases in English rugby union. The seemingly sporadic intervention by the criminal law in on-field ‘violence’ incidents was examined, whilst also considering both the complications encountered when applying criminal proceedings to participator ‘violence’, and whether the RFU might better serve as regulator. The perspectives of twenty participants, nine of whom were interviewed, and eleven of which completed an online questionnaire, were utilised to examine the most effective means of regulation in English rugby union, and the issues attached to using the criminal law as a method of governance. Out of the nine interviewed, three were legal professionals, two were currently referees in the Aviva Premiership, and four were presently RFU disciplinary panel members. The eleven who completed the online questionnaire were all professional players for a club currently competing in the Aviva Premiership. Thematic analysis revealed four major themes, these were: 1) dangerous play is part of the game; 2) disciplinary sanctions and cards are effective deterrents but inconsistent; 3) the courts have a role to play, yet, the RFU may be better suited to regulate; and, 4) establishing a formal link between the law and RFU could help find equilibrium. It was concluded that the RFU seems to be better suited to dealing with all but the most egregious incidents of participator ‘violence’. The borders of suitability were found to be breached when intent to cause serious harm was present. For participants, this was when the criminal law should interfere. Participants also proposed the use of an RFU referral system, whereby the RFU can refer particularly deplorable cases to the police for investigation. Moreover, the disciplinary devices used by the RFU, sanctions and cards, were seen as effective deterrents and punishments, yet, their issuing was seen as inconsistent and in need of reform